De novo sequencing and transcriptome assembly of Arisaema heterophyllum Blume and identification of genes involved in isoflavonoid biosynthesis. Issue 1 (December 2018) - Wang, Chenkai; Zhu, Jinhang; Liu, Miaomiao; Yang, Qingshan; Wu, Jiawen; Li, Zegeng
Abstract Arisaema heterophyllum Blume (AhBl ) is one of the valued medicinal plants. However, its genetic information is limited, which impedes further studies of this valuable resource. To investigate the genes involved in the isoflavonoid biosynthesis, we deeply performed transcriptome sequencing forAhBl . An average of 10.98 Gb clean reads were obtained based on root, tuber and leaf tissues, and 109, 937 unigenes were yielded after de novo assembly. In total, 72, 287 of those unigenes were annotated in at least one public database. The numbers of expressed unigenes in each tissue were 35, 686, 43, 363 and 47, 783, respectively. The overall expression levels of transcripts in leaf were higher than those in root and tuber. Differentially expressed genes analysis indicated that a total of 12, 448 shared unigenes were detected in all three tissues, 10, 215 of which were higher expressed in tuber than that in root and leaf. Besides, 87 candidate unigenes that encode for enzymes involved in biosynthesis of isoflavonoid were identified and analyzed, and some key enzyme genes were experimentally validated by quantitative Real-Time PCR (qRT-PCR). This study provides a unique dataset for the systematic analysis ofAhBl functional genes and expression characteristics, and facilitates the future study of the pharmacological mechanism ofAhBl .